Barrierefreies Übersetzen in Museen: Übersetzungsphasen bei der Erstellung eines inklusiven Audioguides für Sehgeschädigte und Blinde anhand eines Fallbeispiels - Limbach, Christiane (Glottodidactica, 2025)
This article aims to describe the process of creating an audio guide for the blind and visually impaired (AGBVI) from the perspective of translation studies. The distinct phases of the translation process (Neunzig & Tanqueiro 2007) are applied to the process of content creation for the audio guide in order to make it more transparent for translators. The individual steps involved in producing the audio guide for the exhibition Alarifes Ruiz Florindo in Seville (Spain) serve as a practical example. For this reason, the Spanish and mandatory standard UNE 153020 (Aenor 2005) for the creation of audio guides for the visually impaired and blind will also be taken into account, as well as relevant research findings in the field. Based on the discussion and conclusions presented in this article and practical experience, a translation model for AGBVI will be presented. The findings are intended to support translators and professionals involved in creating audio guides for blind and visually impaired audiences in museums, as well as learners and teachers of inclusive translation.